Comprehending Commercial Speech: How 13-15 Year Olds Understand Non-Traditional Advertising on New Zealand Radio - Watts, Thomas (Auckland University of Technology, 2010)
New Zealand’s radio environment is considered one of the most commercially saturated in the developed world. Alongside this has been a rise in non-traditional advertising techniques such as aural product placement, sponsorships and giveaways which are presented as editorial content. This research explores the attitudes and understandings of 13-15 year olds in relation to these new forms of advertising on New Zealand commercial radio. Using a reception studies approach, this research shows that young people are very aware of the heavily commercialised media environment in which they are part of. However, the commercial reality is accepted as a naturalised status quo rather than as institutions that can be influenced. The participants were not necessarily able to identify non-traditional advertising approaches. Ultimately, this research provides an understanding of how growing up in one of the most heavily commercial radio environment in the world affects the experience of the listener.
Keywords: Radio; Commercial; Advertising; Youth; Deregulation; New Zealand